Get off my land! Towards mutual understanding in archaeological field conflicts - Bertram Mapunda (AP, 2017)
Genuine community participation in research and conservation projects is crucial for sustainable protection, management and development of archaeological sites, especially in sub-Saharan Africa where the scientific value of such resources is less appreciated. Local people often become suspicious of and discontented with field researchers who do not inform them of what they are doing around their courtyard, just as they are displeased with government officials who impose conservation projects upon them. Their discontent often comes for good reasons: either the given research or project is not a priority to them or its objectives differ from theirs. As a result, a conflict of expectations emerges, often leading local communities into disliking the project and hence investing little or just superficial commitment to it. Such feelings may be expressed verbally in formal or informal gatherings or through indifference, resentment, or vandalism, all of which are detrimental to the proper management of the heritage resource in question. Using specific cases of researchers/administrators-villagers differences and conflicts of expectations experienced in various places in Tanzania, the paper discusses causes of such differences, critically examines the Community Participatory technique exposing its strengths and weaknesses, as well as suggests solutions and outlining potential benefits should villagers be genuinely incorporated in such undertakings.